Identification d’Hétérakis Gallinarum Isolé Du Poulet De Chair Et Poulet Fermier (Gallus Gallus) Dans Les Localités De Mesra Et ENARO (Mostaganem) - BENDJELLOUL, NOUR El Houda (My University, 2017)
Breeding of farm chicken and broiler chicken is an important source of animal proteins and poverty reduction in many African countries. However, it is subject to multiple difficulties that decrease its productivity. Parasitism, evaluated in the course of our study, is one of the obstacles preventing traditional and semi-industrial poultry farming from having an important economic position. This study concerns 10 farm chickens and 15 boilers collected randomly in different farms in the region of Mostaganem whose mode of extensive and intensive breeding. The aim of this work, carried out at the veterinary laboratory of the wilaya of Mostaganem for the isolation and identification of nematodes Heterakis gallinarum in farm chickens and also isolated a trematode and a cestode. As well as in broiler chickens coccidia have been observed in the cæcum. The results of our histological examination of the worms of Heterakis gallinarum show the presence of histomonas in the spicules in the male as well as in the eggs in the female. Rates of parasitism and infestation vary from one species to another. The preferential localization of Heterakis Gallinarum was studied at the level of caecum. To this end, strict preventive measures need to be taken against parasites.
Keywords: Chicken; Traditional breeding; Semi-industrial breeding; Heterakis gallinarum; Cæcum; Region of Mostaganem.; Poulet; Élevage traditionnel; Élevage semi industriel.; Heterakis gallinarum; Cæcum; Région de Mostaganem